Factors Affecting Adoption of Climate Change Adaptation Strategies by Small Holder Farmers in Mountain and Lowland Agro-ecological Zones of Eastern Uganda - Remigio Turyahabwe; Loy Gumisiriza Turybanawe; Joyfred Asaba; Andrew Mulabbi; Mukisa Geofrey (Universitas Muhammadiyah Surakarta, 2022)
Farmers in tropical rural areas are confronted with several challenges but outstandingly climate change which can only be overcome by adopting to climate change resilience strategies. This study assessed the factors affecting adoption of climate change resilience strategies in Muyembe sub-county, Bulambuli district, Uganda. We used questionnaires, interviews, focused group discussions and field observations to collect the required data, which was analyzed using basic descriptive statistics and logistic regression model. Results indicate that, the dominant climate change resilience strategies adopted in the study were, soil/water conservation (65%), drought resistant crop varieties (59.4%), and irrigation (55.6). Results of the logistic regression indicated that, gender and family size were the most important factors that influenced adoption of climate change resilience strategies with coefficient -0.86 and P0.05, and0.18 and P0.05 respectively. On the other hand, the barriers to adoption of the same by majority farmers were dominated by financial constraints and adulteration of farm inputs at 93.4% and 74% respectively. We concluded that, many farmers are still locked in indigenous practices that have made them vulnerable to climate change effects characterized by low yields, crop failure hence low incomes, poverty and food insecurity. We recommended that, government should support the adaptation strategies to climate change by the smallholder farmers technically by providing both ground and surface water irrigation facilities and financially by providing agricultural loans as well as focusing on promoting awareness and advancing education on climate change to farmers through knowledge and skill sharing platforms such as training, conferences, and seminars.